Oceanic Routing of Wind-Sourced Energy Along the Arctic Continental Shelves - Danielson, Seth L.; Hennon, Tyler D.; Hedstrom, Katherine S.; Pnyushkov, Andrey V.; Polyakov, Igor V.; Carmack, Eddy; Filchuk, Kirill; Janout, Markus; Makhotin, Mikhail; Williams, William J.; Padman, Laurie (Frontiers in Marine Science, 2020)
Data from coastal tide gauges, oceanographic moorings, and a numerical model show that Arctic storm surges force continental shelf waves (CSWs) that dynamically link the circumpolar Arctic continental shelf system. These trains of barotropic disturbances result from coastal convergences driven by cross-shelf Ekman transport. Observed propagation speeds of 600-3000 km day-1, periods of 2-6 days, wavelengths of 2000-7000 km, and elevation maxima near the coast but velocity maxima near the upper slope are all consistent with theoretical CSW characteristics. Other, more isolated events are tied to local responses to propagating storm systems. Energy and phase propagation is from west to east: ocean elevation anomalies in the Laptev Sea follow Kara Sea anomalies by one day and precede Chukchi and Beaufort Sea anomalies by 4-6 days. Some leakage and dissipation occurs. About half of the eastward-propagating energy in the Kara Sea passes the Severnaya Zemlya into the Laptev Sea. About half of the eastward-propagating energy from the East Siberian Sea passes southward through Bering Strait, while one quarter is dissipated locally in the Chukchi Sea and another quarter passes eastward into the Beaufort Sea. Likewise, CSW generation in the Bering Sea can trigger elevation and current speed anomalies downstream in the Northeast Chukchi Sea of 25 cm and 20 cm s-1, respectively. Although each event is ephemeral, the large number of CSWs generated annually suggest that they represent a non-negligible source of time-averaged energy transport and bottom stress-induced dissipative mixing, particularly near the outer shelf and upper slope. Coastal water level and landfast ice breakout event forecasts should include CSW effects and associated lag times from distant upstream winds.